MEMBENTUK KARAKTER SISWA DENGAN DONGENG DIGITAL NUSANTARA - Riberu, Evensius Dimas Hendro; Kurniati, Agusta; Oktaviani, Ursula Dwi; Aristo, Thomas Joni Verawanto (STKIP Persada Khatulistiwa Sintang, 2023)
One of the negative things about implementing online learning is that it makes students dishonest in doing assignments and submitting assignments not on time makes it very difficult for the teacher to give an assessment. This shows a decrease in character values in the current generation. This study aims to create a Media Dongeng Digital Nusantara to shape the character of students. This research is a research and development research using the ADDIE model. The test subjects in this study were two grade elementary school students. The instruments used were interview guidelines, documentation guidelines, document study sheets, questionnaires, and rating scale sheets. Data were analyzed using quantitative and qualitative analysis techniques. The results showed that the content validity level of the product was 0.9 with the criteria (very high). The teacher's response is 100% with the criteria (very high). Student responses get an average result of 88% with the criteria (good). The results of the effectiveness analysis obtained results of 0.000 <0.05 (significant), so that Dongeng Digital's multimedia was feasible and effective to use to shape students' character. The implication of this research is that Media Dongeng Digital Nusantara is packaged in the form of Youtube links, so that teachers can easily share videos with other teachers.